PET imaging of net availability in humans using [11C]MRB: Age, gender and ethnicity effects: Neuroimaging / Normal brain aging. (7th December 2020) - Ding, Yu‐Shin; Wang, Jiacheng; Chen, Jingyun; Babb, James; Rusinek, Henry; ,
Abstract: Background: Understanding the underlying pathological mechanisms of AD is urgently needed to enable the development of effective treatments. Tau pathology emerges decades before amyloid pathology, appearing first in the brainstem (BS); particularly in the locus coeruleus (LC), the source of brain's norepinephrine (NE). Our preliminary data using [ 11 C]MRB have documented an age‐related decline in NE transporters (NET) starting in middle age, suggesting in vivo NET availability is a sensitive biomarker for aging and preclinical stages of AD. This report investigated the age, gender and ethnicity effects on NET availability Method: Coregistration of PET (dynamic [ 11 C]MRB), MRI and the FreeSurfer (FS) atlas images of each individual to generate regional time‐activity curves (TAC) using Firevoxel. Binding potential (BPND ) were determined using MRTM2 (t2* 20 min and k2' 0.021 min ‐1 with occipital as the reference region). Annual percent change (APC) of BPND was calculated based on linear regression ( APC = 100 × ( e m – 1), m: slope) and effects of age, gender and ethnicity on tracer binding were evaluated. Result: For all HC (N=31), with both genders and all races included, the NET availability decline can be observed; e.g., ‐0.4%/yr for BS & ROfac. However, in gender‐separated group analysis [(19M, age 36.2±9.9) vs. (12F, age 36.6±9.0)], there was a significant gender effect for APC (P <0.01) with decline rates faster for M (e.g., ‐0.8%/yr for LTH), starting from mid 30 (p<0.001). Interestingly, out of 16 ROIs, while AA (N=14, age 34±7) had consistently higher regional BPND than white subjects (N=12, age 35±8)(P<0.000), the decline rate was much higher for AA (P<0.00001); e.g., ‐3%/yr in LTH for AA‐M. Conclusion: In addition to our previously determined age effect on MRB‐NET binding, this report further reveals, for the first time, the role of gender and ethnicity effects on NET availability, in the context of the aging brain. A bigger sample size is warranted to investigate these effects on the NET availability.